2005
DOI: 10.1603/0046-225x-34.4.833
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Consequences of Multiple Mating on FemaleSitophilus oryzaeL. (Coleoptera: Curculionidae)

Abstract: The effects of multiple mating on Þtness in the rice weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae), were studied. In the Þrst of a series of experiments, the impact of multiple mating on female Þtness was determined by evaluating the effects of a single mating period with one male, continuous exposure to one male, and continuous exposure to Þve males. Continuous exposure to one male increased lifetime fecundity by extending the period of time progeny were produced compared with a single mating perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
5
24
0
1
Order By: Relevance
“…A reduction of female life span in multiple mating is due to the cost of mating itself, such as physical damage by repeated copulation and aging, and the cost of an increased egg production (Chapman et al 1998;Arnqvist and Nilsson 2000;Yanagi and Miyatake 2003;Campbell 2005). The number of matings is usually, but not always, correlated with egg production in many insect and mite (Kawagoe et al 2001;Orsetti and Rutowski 2003;Campbell 2005;Pappas et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…A reduction of female life span in multiple mating is due to the cost of mating itself, such as physical damage by repeated copulation and aging, and the cost of an increased egg production (Chapman et al 1998;Arnqvist and Nilsson 2000;Yanagi and Miyatake 2003;Campbell 2005). The number of matings is usually, but not always, correlated with egg production in many insect and mite (Kawagoe et al 2001;Orsetti and Rutowski 2003;Campbell 2005;Pappas et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In this treatment the survival of females that had access to males was significantly lower than those without males (Figure 4.2). This has been previously reported in Sitophilus oryzae where continuous exposure of female S. oryzae to one or more males decreased the survival rate significantly as opposed to females that had no access to males (Campbell, 2005). Presumably these females were, somehow, stimulated to deposit all their potential eggs and died soon after.…”
Section: Findings and Comparisons Of Field With Laboratory Emigrant Bsupporting
confidence: 69%
“…This indicates that females mate readily irrespective of their age and that they might be stimulated to lay all their eggs before death. The phenomenon of reduced survival after exposure to one or more males has been observed in Sitophilus oryzae (Campbell, 2005).…”
Section: Locusmentioning
confidence: 95%
“…Progeny size, however, was reduced. Campbell (2005) also found that exposure of one female to five males significantly decreased the number and size of progeny produced. Cay et al (2009) reported that females of Callosobruchus maculatus (F.) (Coleóptera; Bruchidae) kept continuously with males have reduced lifetime egg production compared with females mated once and then isolated from males.…”
Section: Discussionmentioning
confidence: 85%
“…An additional cause may be the effect of multiple matings of males with females. Research by Campbell (2005) on the rice weevil, Siiophilus oryzae L. (Coleóptera: Curculionidae), found that continuous exposure to one male increased tbe lifetime fecundity of females by increasing the period of time that eggs were produced, compared with mating with one male for a specific mating interval. Progeny size, however, was reduced.…”
Section: Discussionmentioning
confidence: 99%